To be, or not to be, that is the Question. Is Sustainability Report Reliable? - Calabrese, Armando; Costa, Roberta; Levialdi Ghiron, Nathan; Menichini, Tamara (European Journal of Sustainable Development, 2017)
The reliability of sustainability report is important for accounting companies’ performance to stakeholders. The issues covered in a sustainability report inform stakeholders of the company sustainability strategies and practices. However, the drawing up of the sustainability report involves the risk of misleading communications for green washing purposes. This topic is much discussed in the scientific literature but, to date, without or with insufficient support of quantitative analyses. This paper focuses on the corporate policies of CO2 reduction, for investigating the existing relations between the reported environmental performance of companies and their CO2 emissions. In order to test the possible subsistence of the green washing practices, the sustainability reports of a sample of 50 Italian companies are analysed. Particularly, the number of environmental indicators of the sustainability reports have been compared with the environmental performance (CO2 emissions) of the companies for investigating if the accuracy and completeness of the sustainability reports are associated with actual sustainable corporate strategies and practices. Keywords: sustainability report; greenwashing; CO2 emissions; GRI